2016
DOI: 10.4196/kjpp.2016.20.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Lnk is an important modulator of insulin-like growth factor-1/Akt/peroxisome proliferator-activated receptor-gamma axis during adipogenesis of mesenchymal stem cells

Abstract: Adipogenic differentiation of mesenchymal stem cells (MSCs) is critical for metabolic homeostasis and nutrient signaling during development. However, limited information is available on the pivotal modulators of adipogenic differentiation of MSCs. Adaptor protein Lnk (Src homology 2B3 [SH2B3]), which belongs to a family of SH2-containing proteins, modulates the bioactivities of different stem cells, including hematopoietic stem cells and endothelial progenitor cells. In this study, we investigated whether an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Activation of the PI3K pathway is triggered by the binding of the receptor to insulin receptor substrate, resulting in the generation of phosphatidylinositol‐3, 4, 5‐triphosphate, which leads to activation of Akt by phosphoinositide‐dependent kinases 27 . The phosphorylated Akt is responsible for the regulation of adipogenic genes via mTOR, that is, the mammalian target of rapamycin 28 . On the other hand, in the MAPK pathway, Ras or SOS, which is an adapter protein, activates ERK1/2; and the phosphorylated ERK1/2 causes upregulation of C/EBPβ/σ expression 29 and activation of PPARγ 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the PI3K pathway is triggered by the binding of the receptor to insulin receptor substrate, resulting in the generation of phosphatidylinositol‐3, 4, 5‐triphosphate, which leads to activation of Akt by phosphoinositide‐dependent kinases 27 . The phosphorylated Akt is responsible for the regulation of adipogenic genes via mTOR, that is, the mammalian target of rapamycin 28 . On the other hand, in the MAPK pathway, Ras or SOS, which is an adapter protein, activates ERK1/2; and the phosphorylated ERK1/2 causes upregulation of C/EBPβ/σ expression 29 and activation of PPARγ 30 .…”
Section: Discussionmentioning
confidence: 99%
“…27 The phosphorylated Akt is responsible for the regulation of adipogenic genes via mTOR, that is, the mammalian target of rapamycin. 28 On the other hand, in the MAPK pathway, Ras or SOS, which is an adapter protein, activates ERK1/2; and the phosphorylated ERK1/2 causes upregulation of C/EBPβ/σ expression 29 and activation of PPARγ. 30 Expression/activation of C/EBPα needs the activation of both C/EBPβ/σ 29 and PPARγ.…”
Section: Ablation Of the Effect Of Lipus On C3h10t1/2 Cells By Ccn2mentioning
confidence: 99%
“…Lee et al showed that IGF-1 participates in the adipogenesis of mesenchymal stem cells by regulating the expression of PPARγ (48). In addition, IGF-1 induces the proliferation and invasion of UM cells by inhibiting Foxo3a (49).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid synthesis is a key nutrient metabolic pathway that allows organisms to remain active even when energy is limited ( Caron et al, 2015 ; Wang et al, 2021 ). Adipogenic differentiation of MSCs is a key developmental process associated with metabolic homeostasis and nutritional signal transduction ( Fernandez-Veledo et al, 2013 ; Lee et al, 2016 ). In adipose cells, mTOR plays a central role in protein synthesis and adipose tissue morphogenesis ( Xiang et al, 2011 ).…”
Section: Effects Of Mammalian Target Of Rapamycin On Mesenchymal Stem...mentioning
confidence: 99%